GPs at the Edge: GATE, a qualitative investigation into the experience of delivering care in Irish Rural General Practice - Robyn Homeniuk; Mike O'Callaghan; Monica Casey; Liam Glynn (James Cook University, 2023)
Introduction: Over a third of Irish people live rurally. However, only a fifth of Irish general practices are located in rural communities and longstanding issues such as distance to other health services, professional isolation, and recruitment and retention of rural healthcare professionals (HCPs) threaten rural general practice’s sustainability. This ongoing study seeks to understand what it is like to provide care to Ireland’s rural and remote populations.Methods: This is a qualitative study, consisting of semi-structured interviews with GPs and practice nurses working in practices that serve rural populations across Ireland. Topic guides were developed after a literature review and a series of pilot interviews. Interviews are scheduled to be finished in February 2022.Results: This study is ongoing so results are yet to be finalised. Initial key themes include a great level of professional satisfaction that GPs and practice nurses experience from caring for entire families from the ‘cradle to grave’ and from the complex issues they face in practice. A rural general practice acts as the medical port-of-call for patients, with both practice nurses and GPs having experiences with emergency and pre-hospital medicine. A key difficulty identified is access to secondary and tertiary care services, with distance to services and high demand as the main barriers.Discussion: Working in rural general practice gives HCPs great professional satisfaction but access to other health services remains a challenge. Final conclusions may be compared with other delegates’ experiences.